Efeitos da concentração sub-inibitória de piperacilina/tazobactam, metronidazol e clindamicina na patogenicidade de Bacteroides fragilis recuperados de infecções intra-abdominais - Marcela Abreu Menezes (2018)
The genus Bacteroides consists of anaerobic bacteria most commonly associated with infectious diseases, particularly B. fragilis. Despite representing only 0.5% of the microbiota of the human colon, this is the anaerobe most often recovered of intra-abdominal infections (IAI), due to your virulence, such as presence of capsule, resistance to oxidative stress, biofilm formation, hemolysin and enterotoxin production and antimicrobial resistance. Piperacillin/tazobactam (PTZ), metronidazole (MET) and clindamycin (CLI) are used in the treatment of infectious diseases by B. fragilis, however in subinhibitory concentrations (sub-MIC) are potentially capable of interfering positively or negatively with their pathogenicity. The objective of this study was to evaluate the effects of sub-MIC of PTZ, MET and CLI on the virulence of B. fragilis. Two clinical strains of B. fragilis isolated from IAI patients were included, in addition to a reference strain (B. fragilis ATCC 25285). In these strains, previously cultivated in the medium without and with sub-MIC of the three antimicrobials, phenotypic tests were performed to investigate changes in cell morphology; hydrogen peroxide resistance; biofilm formation; cell surface hydrophobicity; viability of macrophages; hemagglutination; and hemolytic activity. The presence of hemolysin-encoding genes A, B, C, E and III were also evaluated by polymerase chain reaction. Sub-MIC of MET and CLI caused significant delays in log phase growth of the strains. Sub-MIC of PTZ and MET caused cell morphology changes. Overall, sub-MIC of the three antimicrobials decreased oxidative stress resistance. Sub-MIC of MET decreased the hydrophobicity of the three strains and CLI decreased the hydrophobicity of two strains tested; and sub-MIC of PTZ increased the hydrophobicity of the two clinical strains. Sub-MIC of CLI allowed a greater survival of macrophages cultured with bacterial suspension of two strains. On the other hand, sub-MIC of PTZ reduced the viability of macrophages cultured with bacterial suspension of the three strains, and sub-MIC of MET reduced the viability of macrophages cultured with bacterial suspension of the two clinical strains. All strains showed haemolysis in all blood types tested, except the P34 clinical strain, previously cultured in medium without and with sub-MIC of the three antimicrobials, when tested with sheep's blood. The B. fragilis reference strain and the clinical strains were positive for the five genes tested. Thus, virulence changes lead to the risks of an inadequate antimicrobial therapy, being able to induce different interactions in host-bacteria relationships, besides being able to affect in the diagnosis and treatment of infectious diseases by B. fragilis.